Dynamic changes in β-cell [Ca2+] regulate NFAT activation, gene transcription, and islet gap junction communication - Jose G. Miranda; Wolfgang E. Schleicher; Kristen L. Wells; David G. Ramirez; Samantha P. Landgrave; Richard K.P. Benninger (Elsevier, 2022)
Objective: Diabetes occurs because of insufficient insulin secretion due to β-cell dysfunction within the islet of Langerhans. Elevated glucose levels trigger β-cell membrane depolarization, action potential generation, and slow sustained free-Ca2+ ([Ca2+]) oscillations, which trigger insulin release. Nuclear factor of activated T-cell (NFAT) is a transcription factor, which is regulated by the increases in [Ca2+] and calceineurin (CaN) activation. NFAT regulation links cell activity with gene transcription in many systems and regulates proliferation and insulin granule biogenesis within the β-cell. However, the link between the regulation of β-cell electrical activity and oscillatory [Ca2+] dynamics with NFAT activation and downstream transcription is poorly understood. Here, we tested whether dynamic changes to β-cell electrical activity and [Ca2+] regulate NFAT activation and downstream transcription. Methods: In cell lines, mouse islets, and human islets, including those from donors with type 2 diabetes, we applied both agonists/antagonists of ion channels together with optogenetics to modulate β-cell electrical activity. We measured the dynamics of [Ca2+] and NFAT activation as well as performed whole transcriptome and functional analyses. Results: Both glucose-induced membrane depolarization and optogenetic stimulation triggered NFAT activation as well as increased the transcription of NFAT targets and intermediate early genes (IEGs). Importantly, slow, sustained [Ca2+] oscillation conditions led to NFAT activation and downstream transcription. In contrast, in human islets from donors with type2 diabetes, NFAT activation by glucose was diminished, but rescued upon pharmacological stimulation of electrical activity. NFAT activation regulated GJD2 expression and increased Cx36 gap junction permeability upon elevated oscillatory [Ca2+] dynamics. However, it is unclear if NFAT directly binds the GJD2 gene to regulate expression. Conclusions: This study provides an insight into the specific patterns of electrical activity that regulate NFAT activation, gene transcription, and islet function. In addition, it provides information on how these factors are disrupted in diabetes.